Variability and sampling of lead (Pb) in drinking water: Assessing potential human exposure depends on the sampling protocol. (January 2021) - Triantafyllidou, Simoni; Burkhardt, Jonathan; Tully, Jennifer; Cahalan, Kelly; DeSantis, Michael; Lytle, Darren; Schock, Michael
Highlights: Lead in drinking water can vary widely in space and in time. Different sampling protocols may capture different concentrations from lead sources. Most water sampling protocols cannot accurately represent lead exposure. Composite proportional sampling (automatic, manual or passive) represents exposure. Abstract: Lead ( Pb) in drinking water has re-emerged as a modern public health threat which can vary widely in space and in time (i.e., between homes, within homes and even at the same tap over time). Spatial and temporal water Pb variability in buildings is the combined result of water chemistry, hydraulics, Pb plumbing materials and water use patterns. This makes it challenging to obtain meaningful water Pb data with which to estimate potential exposure to residents. The objectives of this review paper are to describe the root causes of intrinsic Pb variability in drinking water, which in turn impacts the numerous existing water sampling protocols for Pb. Such knowledge can assist the public health community, the drinking water industry, and other interested groups to interpret/compare existing drinking water Pb data, develop appropriate sampling protocols to answer specific questions relating to Pb in water, and understand potential exposure to Pb-contaminated water. Overall, review of the literature indicated that drinking water sampling for Pb assessment can serve many purposes. Regulatory compliance sampling protocols are useful in assessing community-wide compliance with a water Pb regulatory standard by typically employing practical single samples. More complex multi-sample protocols are useful for comprehensive Pb plumbing source determination (e.g., Pb service line, Pb brass faucet, Pb solder joint) or Pb form identification (i.e., particulate Pb release) in buildings. Exposure assessment sampling can employ cumulative water samples that directly capture an approximate average water Pb concentration over a prolonged period of normal household water use. Exposure assessment may conceivably also employ frequent random single samples, but this approach warrants further investigation. Each protocol has a specific use answering one or more questions relevant to Pb in water. In order to establish statistical correlations to blood Pb measurements or to predict blood Pb levels from existing datasets, the suitability of available drinking water Pb datasets in representing water Pb exposure needs to be understood and the uncertainties need to be characterized.